Manajemen Pengasuhan Santri Putri Melalui Program Ta'lim Dalam Pembentukan Akhlak Di Pesantren Darunnajah 2 Cipining Bogor - Siti Chadijah; Lailatul Fitria (At-Takwin: Journal of Islamic Education Studies, 2025)
Pesantren as an Islamic educational institution places moral character formation as its primary goal. However, a gap still exists between the implementation of religious programs and the actual behavioral outcomes of female santri. Purpose: This article examines the management of female santri supervision through the Ta'lim program in moral character formation at Pesantren Darunnajah 2 Cipining, Bogor. Methods: Qualitative descriptive approach, data collected through observation, in-depth interviews, and documentation. Results: Supervision management through the Ta'lim program encompasses four managerial functions—planning, organizing, implementation, and evaluation—integrated within a 24-hour system. The program effectively cultivates Islamic values including worship discipline, social ethics, honesty, and obedience. Conclusions: Success is determined by supervision management quality, musyrifah competence, and value integration consistency.